2019
DOI: 10.1186/s12885-019-6447-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival status and associated factors of death among cervical cancer patients attending at Tikur Anbesa Specialized Hospital, Addis Ababa, Ethiopia: a retrospective cohort study

Abstract: BackgroundCervical cancer is a cancer of uterine cervix caused mostly by sexually-acquired infection called Human papillomavirus (HPV. In developing region of the globe, fewer than 50% of women with cervical malignancy survive more than 5 years. Therefore, the objective of this study was to assess survival status and associated factors of death among cervical cancer patients attending at Tikur Anbesa Specialized Hospital (TASH), Ethiopia.MethodsFacility based retrospective cohort study was conducted from March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
4
24
0
2
Order By: Relevance
“…Patients who presented with advanced stage died more than those with early stage. This result is in line with the studies conducted in New Zealand [ 33 , 34 ]. The increment of mortality could be as the cancer stage getting advanced, its metastasis rate could be increased and these factors might decrease the probability to respond a treatment and lead to death [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Patients who presented with advanced stage died more than those with early stage. This result is in line with the studies conducted in New Zealand [ 33 , 34 ]. The increment of mortality could be as the cancer stage getting advanced, its metastasis rate could be increased and these factors might decrease the probability to respond a treatment and lead to death [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…With the current treatment capacity limitations, outcomes for early stage disease are generally poorer in Africa, with a reported 2-year overall survival of 50% for stage IeIIA cervical cancer in Nigeria and a median overall survival of 21 and 15 months for stage I and II cervical cancer, respectively, in a cohort of radiationtreated patients in Kenya [29,30]. However, some hospitals report better outcomes, such as 5-year overall survival of 80% for stage I and 69% for stage II cervical cancer in a hospital in Ethiopia [31]. A review of population-based registries from nine African countries revealed a 5-year overall survival of 50.3% for stage IeII cervical cancer [14].…”
Section: Africamentioning
confidence: 99%
“…Quick scale-up of immunization and double lifetime uterine cervix screening in the world could prevent up to 13.4 million malignancies over the long run half century [ 19 , 20 ]. Additionally, early diagnosis and managing other factors will decrease mortality and also the prevalence among those patients [ 21 ]. So, this systematic review and meta-analysis aimed is to identify pooled prevalence and determinants of late-stage presentation among cervical cancer patients.…”
Section: Introductionmentioning
confidence: 99%